Analysis of Factors Influencing Satisfaction of BYOND By BSI Application Users in DKI Jakarta - Renandia Chandra Putri; Osly Usman; Adnan Kasofi (Takaza Innovatix Labs Ltd., 2026)
Digital banking adoption in Indonesia reaches 80.7% penetration (APJII, 2025), yet BYOND by BSI faces user dissatisfaction post-rebranding despite 3.5 million users, with prior studies showing inconsistent TAM factor effects on Islamic mobile banking satisfaction in urban contexts. This study analyzes the influence of perceived usefulness (X1), ease of use (X2), security (X3), and enjoyment (X4) on user satisfaction (Y) of BYOND by BSI in DKI Jakarta through quantitative cross-sectional survey of 230 purposive respondents (Gen Y dominant, 60% female) from active users (≥6 months), using Likert-6 Google Forms analyzed via SmartPLS 4.0 SEM-PLS with validated reflective measurement (AVE>0.5, CR>0.9, HTMT<0.90, VIF<5). All hypotheses were accepted (p<0.05): X4 (β=0.233, highest), X1 (β=0.236), X3 (β=0.269), X2 (β=0.206, lowest), explaining 59.6% satisfaction variance (adj.R²=0.596; Q²=0.544, large). Hybrid TAM-affective model is confirmed for syariah mobile banking optimization, prioritizing enjoyment and security enhancements.